Kierikki Stone Age Centre – The Advantages of Being an OpenArch Funded Project - Leena Lehtinen (EXARC Journal)
Compared to other European countries, the number of Finnish archaeological open-air museums is limited. Currently, Kierikki and Saarijärvi Stone Age villages are the only two open-air museums under the care of professional museums. Both villages specialise in the Stone Age period (Kierriki 2015; Saarijärvi 2015). Apart from these two museums, Finland also has a couple of reconstructions of Viking age houses, however these do not fall under any museum care. Since 2013, Kierikki forms part of the Museum and Science Centre Luuppi, City of Oulu.